Membangun Masa Depan Pendidikan: Peran kepemimpinan Visioner Dalam Meningkatkan Kualitas Pendidikan - Annisa Annisa; M. Imamul Muttaqin (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
This research discusses the importance of visionary leadership in improving the quality of education in a challenging global and local era. Through a literature study approach, this research analyzes various theories and findings related to the role of leadership in education. The results show that visionary leadership has a significant influence on improving the quality of education through innovation, long-term vision and adaptability. The research also identifies the main characteristics of effective visionary leadership and implementation strategies that can be applied in educational institutions. The conclusion of this study confirms that the implementation of visionary leadership is essential to build a quality and sustainable future for education.